The haunted culture—Shamanic heroes in the cultural content industry of South Korea - Seo, Jinseok (Acta Orientalia Vilnensia, 2011)
Vytautas Magnus UniversityKorea, with insufficient natural resources and a limited consumer market, began to take notice of the cultural content industry in the 21st century. This means that the cultivation of this industry has not taken place for a long time compared to Japan, the USA or Hong Kong. Yet Korea has obtained an astonishing outcome in a short time. The popular culture of South Korea, with the appellation of hallyu, boasted of an enormous strength initially in the Asian market and subsequently stretched to markets in other countries, too. Seeing that Korean cultural archetypes do not play a successful role in the cultural content business of Korea in general, the position of shamanism is truly trivial among the others. I would like to analyse and discuss the meaning, function and potential of Korean shamanism in the field of the Korean cultural content industry.